Mechanical properties of human glioma. (1st December 2020) - Tsitlakidis, Abraham; Aifantis, Elias C.; Kritis, Aristeidis; Tsingotjidou, Anastasia S.; Cheva, Angeliki; Selviaridis, Panagiotis; Foroglou, Nicolas
ABSTRACT: Brain gliomas represent some of the most aggressive tumors encountered by modern medicine and, despite major efforts to optimize early diagnosis and treatment, the prognosis remains poor. Due to the complex structure of the brain and the unique mechanical properties of the extracellular matrix, gliomas invade and expand into the brain parenchyma, along white matter tracts and within perivascular spaces, usually sparing normal vessels. Different methods have been developed to study the mechanical properties of gliomas in a wide range of scales, from cells and the microscale to tissues and the macroscale. In this review, the current view on glioma mechanics is presented and the methods used to determine glioma mechanical properties are outlined. Their principles and current state of affairs are discussed.